2017
DOI: 10.1140/epjc/s10052-017-5185-y
|View full text |Cite
|
Sign up to set email alerts
|

Three-forms in supergravity and flux compactifications

Abstract: We present a duality procedure that relates conventional four-dimensional matter-coupled N = 1 supergravities to dual formulations in which auxiliary fields are replaced by field strengths of gauge three-forms. The duality promotes specific coupling constants appearing in the superpotential to vacuum expectation values of the field strengths. We then apply this general duality to type IIA string compactifications on Calabi-Yau orientifolds with RR fluxes. This gives a new supersymmetric formulation of the corr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
151
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(164 citation statements)
references
References 65 publications
(188 reference statements)
3
151
0
Order By: Relevance
“…In particular, the relation between axion potentials and three‐forms as been developed in [] and utilised in the context of inflation in []. This relation has been extensively studied in string theory in a recent program of work [].…”
Section: The Emergence Proposalmentioning
confidence: 99%
“…In particular, the relation between axion potentials and three‐forms as been developed in [] and utilised in the context of inflation in []. This relation has been extensively studied in string theory in a recent program of work [].…”
Section: The Emergence Proposalmentioning
confidence: 99%
“…Complex three-form supergravity [48,52,55] is obtained by choosing the prepotential P in (5.1) to have the form P = Γ +Γ , (5.5)…”
Section: Jhep04(2018)131mentioning
confidence: 99%
“…These theories provide an effective supergravity description of type II string compactifications on Calabi–Yau manifolds with Ramond‐Ramond fluxes. In particular, in [] it has been shown that the scalar potential obtained from compactifications of Type IIA string theory is retrieved from and that the tension of the membrane is equal to that of membranes obtained from wrapping higher dimensional branes over special Lagrangian cycles in the Calabi–Yau.…”
Section: Discussionmentioning
confidence: 99%
“…In what follows, we will briefly review the results of [] on the description of these effective theories within a generic 4D N=1 supergravity containing multiple three‐form gauge fields coupled to membranes.…”
Section: Relaxing the Cosmological Constant By Membrane Nucleationmentioning
confidence: 99%
See 1 more Smart Citation